Low-Grade Appendiceal Mucinous Neoplasms: A Single Institution Experience of 64 Cases With Clinical Follow-up and Correlation With the Current (Eighth Edition) AJCC Staging. (May 2020) - Wong, Mary; Barrows, Brad; Gangi, Alexandra; Kim, Stacey; Mertens, Richard B.; Dhall, Deepti
Background . In this single-institution study, we applied the current (eighth edition) American Joint Committee on Cancer pathologic staging criteria to 64 low-grade mucinous neoplasms of the appendix (LAMNs), examined their histopathologic features, and studied the patients' clinical outcomes. Design . Sixty-four LAMNs, with a median follow-up of 52 months, were reviewed. Results . The distribution of pathologic stages was pTis (n = 39), pT3 (n = 1), pT4a (n = 5), pT4aM1a (n = 8), and pT4aM1b (n = 11). Recurrence was observed in only 2 patients (both with pT4aM1b disease), one of whom died of disease. All remaining patients were disease-free after a median clinical follow-up of 60 months. Conclusions . Our study confirms that pTis LAMNs have an excellent prognosis and suggests that pT4a and pT4aM1a LAMNs may also have a low risk of developing progressive disease.